Persistent Protein Motions in a Rugged Energy Landscape Revealed by Normal Mode Ensemble Analysis - Romo, T. D.; Grossfield, A.; Markelz, A. G. (Journal of Chemical Information and Modeling, 2020)
Proteins are allosteric machines that couple motions at distinct, often distant, sites to control biological function. Low-frequency structural vibrations are a mechanism of this long-distance connection and are often used computationally to predict correlations, but experimentally identifying the vibrations associated with specific motions has proved challenging. Spectroscopy is an ideal tool to explore these excitations, but measurements have been largely unable to identify important frequency bands. The result is at odds with some previous calculations and raises the question what methods could successfully characterize protein structural vibrations. Here we show the lack of spectral structure arises in part from the variations in protein structure as the protein samples the energy landscape. However, by averaging over the energy landscape as sampled using an aggregate 18.5 mu s of all-atom molecular dynamics simulation of hen egg white lysozyme and normal-mode analyses, we find vibrations with large overlap with functional displacements are surprisingly concentrated in narrow frequency bands. These bands are not apparent in either the ensemble averaged vibrational density of states or isotropic absorption. However, in the case of the ensemble averaged anisotropic absorption, there is persistent spectral structure and overlap between this structure and the functional displacement frequency bands. We systematically lay out heuristics for calculating the spectra robustly, including the need for statistical sampling of the protein and inclusion of adequate water in the spectral calculation. The results show the congested spectrum of these complex molecules obscures important frequency bands associated with function and reveal a method to overcome this congestion by combining structurally sensitive spectroscopy with robust normal mode ensemble analysis.
ISI Document Delivery No.: PT8QA Times Cited: 0 Cited Reference Count: 47 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Bahar I, 2007, CURR OPIN STRUC BIOL, V17, P633, DOI 10.1016/j.sbi.2007.09.011 Balog E, 2011, J PHYS CHEM B, V115, P6811, DOI 10.1021/jp108493g Castro-Camus E, 2008, CHEM PHYS LETT, V455, P289, DOI 10.1016/j.cplett.2008.02.084 Cerutti DS, 2008, BIOCHEMISTRY-US, V47, P12065, DOI 10.1021/bi800894u Cerutti DS, 2019, WIRES COMPUT MOL SCI, V9, DOI 10.1002/wcms.1402 CHO M, 1994, J CHEM PHYS, V100, P6672, DOI 10.1063/1.467027 Choi JH, 2014, J PHYS CHEM B, V118, P12837, DOI 10.1021/jp508547y Cote Y, 2017, BIOPHYS J, V112, P2575, DOI 10.1016/j.bpj.2017.05.018 Dong J, 1999, ACTA CRYSTALLOGR D, V55, P745, DOI 10.1107/S0907444998016047 ESSMANN U, 1995, J CHEM PHYS, V103, P8577, DOI 10.1063/1.470117 Falconer RJ, 2012, J INFRARED MILLIM TE, V33, P973, DOI 10.1007/s10762-012-9915-9 FELLER SE, 1995, J CHEM PHYS, V103, P4613, DOI 10.1063/1.470648 Gerek ZN, 2011, PLOS COMPUT BIOL, V7, DOI 10.1371/journal.pcbi.1002154 GO N, 1983, P NATL ACAD SCI-BIOL, V80, P3696, DOI 10.1073/pnas.80.12.3696 Grossfield A, 2019, LIVING J COMPUT MOL, V1, P5067, DOI DOI 10.33011/LIVEC0MS.1.1.5067 Grossfield A, 2009, ANN REP COMP CHEM, V5, P23, DOI 10.1016/S1574-1400(09)00502-7 He YF, 2011, BIOPHYS J, V100, P1058, DOI 10.1016/j.bpj.2010.12.3731 HORIUCHI T, 1991, PROTEINS, V10, P106, DOI 10.1002/prot.340100204 Huang J, 2013, J COMPUT CHEM, V34, P2135, DOI 10.1002/jcc.23354 Katebi AR, 2014, PROTEIN SCI, V23, P213, DOI 10.1002/pro.2407 Kindt JT, 1997, J CHEM PHYS, V106, P4389, DOI 10.1063/1.473486 Kroll J, 2007, VIB SPECTROSC, V43, P324, DOI 10.1016/j.vibspec.2006.03.010 Leioatts N, 2012, J CHEM THEORY COMPUT, V8, P2424, DOI 10.1021/ct3000316 Lerbret A, 2009, J CHEM PHYS, V131, DOI 10.1063/1.3273218 Meinhold L, 2007, PHYS REV LETT, V99, DOI 10.1103/PhysRevLett.99.138101 Miller DW, 1999, J MOL BIOL, V286, P267, DOI 10.1006/jmbi.1998.2445 Niessen KA, 2019, NAT COMMUN, V10, DOI 10.1038/s41467-019-08926-3 Niessen KA, 2017, BIOPHYS J, V112, P933, DOI 10.1016/j.bpj.2016.12.049 Phillips JC, 2005, J COMPUT CHEM, V26, P1781, DOI 10.1002/jcc.20289 Porter JR, 2019, BIOPHYS J, V116, P818, DOI 10.1016/j.bpj.2018.11.3144 Romo TD, 2014, J COMPUT CHEM, V35, P2305, DOI 10.1002/jcc.23753 Romo TD, 2009, IEEE ENG MED BIO, P2332, DOI 10.1109/IEMBS.2009.5335065 Sassi P, 2013, J CHEM PHYS, V139, DOI 10.1063/1.4838355 Singh R, 2012, J PHYS CHEM A, V116, P10359, DOI 10.1021/jp307288r Stehle CU, 2012, J CHEM PHYS, V136, DOI 10.1063/1.3686886 STRAUB JE, 1994, J PHYS CHEM-US, V98, P10978, DOI 10.1021/j100093a046 Tehver R, 2009, J MOL BIOL, V387, P390, DOI 10.1016/j.jmb.2008.12.032 Thirumuruganandham SP, 2009, J MOL MODEL, V15, P959, DOI 10.1007/s00894-008-0446-1 Whitmire SE, 2003, BIOPHYS J, V85, P1269, DOI 10.1016/S0006-3495(03)74562-7 Xie AH, 2000, PHYS REV LETT, V84, P5435, DOI 10.1103/PhysRevLett.84.5435 Xu D, 1996, J PHYS CHEM-US, V100, P12108, DOI 10.1021/jp960076a Yu X, 2005, J CHEM PHYS, V122, DOI 10.1063/1.1830431 Yu X, 2004, CHEM PHYS LETT, V391, P181, DOI 10.1016/j.cplett.2004.04.100 Zakaria HA, 2011, APPL SPECTROSC, V65, P260, DOI 10.1366/10-06162 Zhang HL, 2009, J MOL GRAPH MODEL, V27, P655, DOI 10.1016/j.jmgm.2008.10.005 Zorba A, 2019, P NATL ACAD SCI USA, V116, P13937, DOI 10.1073/pnas.1906024116 Romo, Tod D. Grossfield, Alan Markelz, Andrea G. Grossfield, Alan/0000-0002-5877-2789 National Science FoundationNational Science Foundation (NSF) [MCB 1616529]; U.S. Department of EnergyUnited States Department of Energy (DOE) [DESC0016317] Funding was provided by the National Science Foundation (MCB 1616529) and the U.S. Department of Energy (DESC0016317). 1 Amer chemical soc Washington 1549-960x
Keywords: Chemistry; Computer Science; molecular-dynamics; Pharmacology & Pharmacy; photoactive yellow protein; spectroscopy; state; vibrational-modes